Malignant melanoma of the ear - a literature review of a rare otological tumor - Nicol Dardzińska; Marta Dziedziak; Aleksandra Grzegorczyk; Natalia Hopej; Justyna Korus (Journal of Education, Health and Sport)
The purpose of this article is to raise awareness of a malignant melanoma which is usually associated with a location on the exposed skin and occurs rarely in the area of the ear. Ear as an organ is divided into three parts - external, middle and inner ear. In each of these parts the process of carcinogenesis can occur. The tumor develops from mutated melanocytes. External ear melanoma contributes for only about 1% of all cutaneous melanoma and occurs mostly to people over the age of 60. Lesions in this area should raise concern and a detailed differential diagnosis should be implemented. The main treatment method is surgery, however due to rarity of the tumour no standard approach has been presented. A rarer location is malignant melanoma in the middle and inner ear, which can extend to the Eaustachian tube. There are barely a few cases described in the English literature so far. Symptoms include ear discharge, hearing impairment, and a sensation of fullness in the affected ear. As well as in the tumor of the external ear, also in this case, there are no standard procedures. However it is suggested to choose the surgical approach that can be combined with both radiotherapy and chemotherapy. The prognosis remains poor despite the significant development of medicine.